Scientific School of Management Theory - G. R. Latfullin (Управление)
With man’s appearance on the earth everything of his existence, functioning and development was provided by a targeted impact on the environment. Expressing this impact the process of setting and achieving goals is now defined as a universal management of the widest range of objects, most notably human society. Naturally, this process became a matter of practical observation, applied research, theory building, causing over time, formation of management science. The initiator, founder and organizer of the first in our country scientific school of management theory and of the Department, got in the beginning, the name “Scientific fundamentals of production management” of the Moscow Engineering Economic Institute, became doctor of economic Sciences, Professor Kozlova Olympiada Vasil’evna. She united and directed the research and teaching activities of scientists and practitioners to the design, development and application of holistic management theory. Today it has become one of the fundamental principles of presentation and development of contemporary management science.